2002
DOI: 10.1021/ja028835s
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Photogenerated Radicals in Thin Polymer Films:  Fluorescence Imaging Using a Prefluorescent Radical Probe

Abstract: Prefluorescent radical probes, in which fluorescence is activated by radical trapping, and photoinitiators were used to detect radical generation in polymer films using fluorescence spectroscopy and microscopy. Prefluorescent radical probes are the foundation of a fluorescence imaging system for polymer films, that may serve both as a mechanistic tool in the study of photoinitiated radical processes in polymer films and in the preparation of functional fluorescent images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
93
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(94 citation statements)
references
References 28 publications
0
93
0
1
Order By: Relevance
“…A tether between the fluorophore and the radical moiety increases encounters between the fluorophore and the radical, which increases the efficacy of fluorescence quenching. Much work has been done on these tethered units, initially by Blough et al [2][3][4][5][6][7] and more recently by Scaiano et al [8][9][10] Both groups demonstrated that, in the presence of the nitroxide radical, fluorescence is substantially reduced. Loss of the spin by radical trapping, or redox activity, removes this quenching effect, and the fluorescence of the molecule can then be observed.…”
Section: Introductionmentioning
confidence: 99%
“…A tether between the fluorophore and the radical moiety increases encounters between the fluorophore and the radical, which increases the efficacy of fluorescence quenching. Much work has been done on these tethered units, initially by Blough et al [2][3][4][5][6][7] and more recently by Scaiano et al [8][9][10] Both groups demonstrated that, in the presence of the nitroxide radical, fluorescence is substantially reduced. Loss of the spin by radical trapping, or redox activity, removes this quenching effect, and the fluorescence of the molecule can then be observed.…”
Section: Introductionmentioning
confidence: 99%
“…As many intermolecular quenching mechanisms rely on chance collisions between an excited molecule and the nitroxide radical, the linking together of these moieties increases the rate of interaction which subsequently enhances the efficacy of fluorescence quenching. Work by Blough [5][6][7][8][9][10] and Scaiano [11][12][13] has shown that fluorescence is significantly reduced in the presence of a nitroxide radical. Following radi-cal trapping or redox activity, a diamagnetic species is formed and normal fluorescence emission is restored.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the nitroxide-fluorophore adducts synthesized to date possess potentially labile linkages such as esters, [5][6][7]11,[14][15][16][17][18] amides [19][20][21] or sulfonamides. [22][23][24][25] Cleavage of the nitroxide moiety from the fluorophore restores fluorescence independently from the radical reactions of the nitroxide.…”
Section: Introductionmentioning
confidence: 99%
“…The quenching mode operative in the paramagnetic probe is lost, and the emission is restored, corresponding to a trapped or "on" state. There are a number of examples in the literature where this methodology has been applied to the study of radicals in other types of heterogeneous systems, e.g., polymers, micelles [114][115][116][117].…”
Section: Monitoring Intrazeolite Radical Reactionsmentioning
confidence: 99%